Case Report: How an Iliac Vein Lesion During Totally Endoscopic Preperitoneal Repair of an Inguinal Hernia Can Be Safely Managed - Tabriz, Navid; Uslar, Verena Nicole; Cetin, Timur; Marth, Andreas; Weyhe, Dirk (Frontiers in Surgery, 2021)
Inguinal hernia repair is a common surgical procedure with an acceptably low complication rate. However, complications with potentially life-threating consequences may occur in rare cases. These complications might be very challenging to manage, even more in laparo-endoscopic interventions compared to open repair. One of these challenges can be the treatment of an intraoperative injury to the iliac vein. To the best of our knowledge, a lesion of the iliac vein during TEP (totally endoscopic preperitoneal) for inguinal hernia repair, and a safe technique for its management have not been reported yet. We report the case of a 75-year-old male patient with previous abdominal surgery scheduled for TEP repair of an inguinal hernia. During surgery, the iliac vein was damaged. If we had performed a laparotomy in this situation, the potentially life-threatening condition of the patient could have deteriorated further. Instead, to avoid a potential CO2 associated embolism, the preperitoneal pressure was gradually reduced, and the positive end expiratory pressure (PEEP) was increased in the manner that a balance between excessive bleeding and potential development of a CO2 embolism was achieved. The injured vein was sutured endoscopically, and in addition a hemostatic patch was applied. We then continued with the planned surgical procedure. Thrombosis of the sutured vein was prevented by prophylactic administration of low molecular weight heparin until the 14th postoperative day. We conclude that in case of major vein injury during TEP, which might happen irrespective of prior abdominal surgery, the preperitoneal pressure and PEEP adjustment can be used to handle the complication.